Effect of bottom friction on tidal hydrodynamics along Gulf of Khambhat, India. (5th March 2015) - Sathish Kumar, S.; Balaji, R.
Abstract: Tides play a vital role in coastal hydrodynamics, and it is important to understand their complex characteristics in the coastal areas of creeks, bays, estuaries and gulf. In this study, the spatial variation of heterogeneous friction coefficients and their influence on the variation of different tidal constituents (K1, M2, N2, O1, P1 and S2) along Gulf of Khambhat, west coast of India, were studied. A two-dimensional finite element-based numerical model was developed and zones of different friction coefficients were identified by comparing numerically estimated tidal levels and currents with that of measured and reported by earlier studies. Based on the comparisons, the gulf was divided into five zones of different bottom friction values. The numerical model, assigned with friction coefficients, was used to map the contours of selected tidal constituents. From the results, it was observed that two constituents, M2 and K1, influence the hydrodynamics, significantly. The description of the numerical model, calibration, validation and results are presented in this paper.